Are Universities Aware of the Changes that are Occurring in Higher Education? - Francisco José GARCÍA PEÑALVO (Ediciones Universidad de Salamanca, 2017)
The editorial of this last issue of volume 17, corresponding to 2016, reflects about the vertiginous changes that are taking place in higher education, with management and business models based on online education and a labour market orientation that challenge the traditional concept of University. The underlying question is whether the University, as an institution, is aware of all these movements and is prepared to give a qualified response that allows it to adapt to the new realities of a Digital Society, without losing its hegemony as universal guarantor of the generation and transmission of scientific and humanistic knowledge; or, on the contrary, faithful to its more conservative tradition, it continúes to reinforce the scaffolding of its ivory tower, moving further and further from this reality, secure from a position of social privilege that it understands immovable.